Social policy strategies to combat income poverty of children and families in Europe - Bea Cantillon; Karel Van den Bosch (Luxembourg Income Study (LIS), 2002)
In the EU there is growing concern about poverty among children, and among families with children. In most OECD countries, income poverty among children now exceeds that among the elderly, who traditionally were the demographic group most at risk of poverty (Jäntti and Danziger, 2000). However, the policy response of most industrialized countries in the past decades towards poverty among the elderly - extending coverage and levels of pension benefits - is less obvious as a policy option as regards poverty among families with children. There are two basic reasons for this. First of all, there is a consensus that increases in social spending are to be avoided, in view of the expected upward pressure on government budgets resulting from the ageing of the population in the coming decades. Secondly, in contrast to the elderly, families with children are supposed to be self-reliant, i.e. to be able - in normal circumstances - to earn sufficient income through their own efforts to escape poverty. Benefit dependency is seen as economically inefficient, as socially and morally degrading, and also as ultimately an ineffective route to escape poverty. Given this starting point, this paper tries to reach some general policy recommendations for combating income poverty among children and families. It is organized as follows. In the next section, families with children are most at risk of poverty are identified. Single parents obviously belong to this category, but - what is less well known - so do families with three or more children. There is then discussion of some of the new social risks leading to child poverty, which are related to low skills and to the current impossibility of many parents to combine care for children and paid work. In the fourth and final section, there is suggestions for possible policy responses which would support families in meeting the direct and indirect costs of children.
Keywords: 330; Sozialpolitik; Armutsbekämpfung; Armut; Familie; Kinder; EU-Staaten